2022
DOI: 10.7759/cureus.27746
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis-Associated Anemia: A Narrative Review

Abstract: Tuberculosis (TB) is an airborne illness that induces systemic inflammation. It often affects the lungs causing cough, fever, and chest pain. A commonly associated comorbid condition in TB is anemia. This review article has summarized various studies with an aim to gain a better understanding of pathogenesis and the role of cytokines that contribute to the development of anemia in TB. The study has gathered risk factors that enhance the likelihood of TB patients acquiring anemia. It has reviewed therapeutic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The severity of anemia was unrelated to age or sex. These findings are consistent with those of Dasaradhan et al [ 13 ], Chhabra et al [ 14 ], and de Mendonça et al [ 15 ], who reported that anemia occurs in 61.53-85.7% of TB patients. Patients are anemic because they are malnourished due to the energy expended on combating TB.…”
Section: Discussionsupporting
confidence: 93%
“…The severity of anemia was unrelated to age or sex. These findings are consistent with those of Dasaradhan et al [ 13 ], Chhabra et al [ 14 ], and de Mendonça et al [ 15 ], who reported that anemia occurs in 61.53-85.7% of TB patients. Patients are anemic because they are malnourished due to the energy expended on combating TB.…”
Section: Discussionsupporting
confidence: 93%
“…Anemia is the most common comorbidity in TB ( 21 ). In this study, 48.59% (947/1,949) of the TB patients with sputum smear-positive had anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia impairs the host’s defense against TB infection and increases susceptibility to infection [ 30 , 31 ]. The risk of developing TB for anemic children was 2.87 times higher compared to non-anemic children.…”
Section: Discussionmentioning
confidence: 99%